Creating a virtual device for processing the results of sorption measurements in the study of zinc oxide nanorods - E. V. Maraeva; N. V. Permiakov; Y. Y. Kedruk; L. V. Gritsenko; Kh. A. Abdullin (Chimica Techno Acta, 2020)
The work is devoted to the creation of a virtual device (computer program) for processing the results of sorption analysis of nanomaterials, including for estimating the size of nanoparticles based on the specific surface area. The obtained evaluation results were compared with the scanning electron microscopy data. Photocatalytically active zinc oxide samples were chosen as the object of the study.